NASYID IN MACASSAR LANGUAGE - Muh Kurniawan (Universitas Negeri Makassar, 2021)
A Nasyid is a type of music that has existed in Indonesia for decades. The nasyid is an art form performed by a group consisting of several people. This nasyid is performed in Acapella and contains religious verses and reminds of goodness. In its development, nasyid music experienced ups and downs in the Indonesian music scene. Nasyid music (in acapella format) is now emerging and drowning in nasyid music itself. This journal offers a solution in response to this. Local language nasyid music is one solution in preserving nasyid in the community. It is intended so that the presentation of nasyid can be enjoyed by everyone, and the message of goodness in nasyid music can reach people. Local language nasyid music is expected to bring nasyid music closer to people familiar with local languages. The foreign impression on nasyid music can be removed, and it is hoped that the community will accept it. The local-language nasyid can be a medium for preserving local languages in the community. Among so many nasyid music in local languages produced and circulated in the community, it is expected that the younger generation could be more familiar with the local wisdom in the form of local languages. As well as becomes entertainment contain positiveness in the form of kindness messages from the song lyrics.